Predictors of Remission of Early-Onset Poststroke Depression and the Interaction Between Depression and Cognition During Follow-Up - Huang, Jing; Zhou, Fu-Chun; Guan, Boyuan; Zhang, Ning; Wang, Anxin; Yu, Ping; Zhou, Lei; Wang, Chuan-Yue; Wang, Chunxue (Frontiers in Psychiatry, 2019)
Objectives: This study aimed to examine the rate of remission in individuals experiencing early-onset post-stroke depression (PSD) in China and to identify predictors of remission during 3-month follow-up. This study also tried to explore the interaction between cognitive impairment and depression. Methods: A total of 820 patients with PSD from a massive multi-centered prospective cohort project in China (PRIOD) were included in the present study. Depressive symptoms were measured with Hamilton Depression Rating Scale (17 Items, HDRS-17) at 2 weeks and the endpoint of the 3-month follow-up. The cut-off score of HDRS-17 (<8) was used to define remission of depression at the endpoint. Mini-mental state exam (MMSE) was used to evaluate cognitive impairment of the patients (at 2 weeks follow up and endpoint). The National Institutes of Health Stroke Scale (NIHSS) was used to measure the severity of Stroke. Results: (1) Six hundred and forty-two patients completed the 3-month follow-up, and 332 (51.7%) remitted by the end of the study. Univariate analyses indicated there was a higher proportion of patients who had hypertension, poor outcome at 2 weeks, high scores on NIHSS at 2 weeks，major life events within 3 months, and major medical diseases at 3 months in the non-remission group. In stepwise multiple logistic regression analyses, remission was significantly predicted by lower NIHSS scores at 2 weeks (p < 0.001, OR=1.096, 95% CI 1.045-1.149), fewer major life events (p = 0.024, OR=5.855, 95% CI 1.263-27.131), and fewer major medical comorbidities (p = 0.022, OR 2.307, 95% CI 1.131-4.703). (2) After controlling for NIHSS, hypertension, major life events and medical comorbidities, repeated measures analysis of variance revealed a significant interaction between time (2 weeks vs. endpoint) and group (remitters vs. non-remitters) for MMSE (F(1, 534) =20.4, p < 0.001). Conclusions: Early-onset PSD patients who have milder neurological impairment, fewer major life events and fewer major medical comorbidities at baseline are more likely to achieve remission 3 months after stroke. Only remitters of PSD improved significantly in cognitive impairment after stroke.